Pengaruh Good Corporate Governance Dan Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan LQ 45 - Ummul Khair; Hernadianto Hernadianto; Yusmaniarti Yusmaniarti; Anes Rasela (UNIVED Press, 2023)
The value of the company will continue to increase when the company pays attention to economic, social and environmental aspects. Basically, when the company can achieve short-term and long-term goals, then the company can be said to be good. If the stock gets higher then its value will also be high and have a positive impact on increasing market confidence, not only on current market confidence, but also on the company's future prospects. The purpose of this study is to determine how CSR and GCG affect directly and indirectly on company value with profitability as a moderation variable. This research was conducted on Company LQ 45 which was listed on the Indonesia Stock Exchange in 2019 – 2020. The samples in this study based on the purposive sampling method and obtained 66 sample companies using statistical test data analysis techniques and Partial Least Squarel (PLS). The results of this study show that Good Corporate Governance (GCG) has an insignificant and positive effect on company value by showing that the T-statistical value for the good corporate governance variable is 0.778, the p-value is 0.437>0.05, and the T-table value is 1.669 and the original value is -0.100. The results of the Corporate Social Responsbility (CSR) research had a significal and positive effect on company value measured by CSR disclosures were 2,025, p-value was 0.043<0.05 and T-table value was 1.669 with an original value of 0.192. The results of profitability research did not have a significant effect on the value of the company showing that the T-statistic was 1.135, the p-value was 0.257>0.05 and the T-table value was 1.669 with the original value of -0.138. Meanwhile, the results of the study that Good Corporate Governance (GCG) through profitability has a Tstatistk value of 0.083.p-value of 0.934, and a T-table value of 1.669 with an original value of 0.011 and indirectly GCG has an insignificant effect on company value with profitability as a moderation variable, and the results showed that the Corporate Social Responsibility (CSR) variable through profitability has a T-statistical value of 1.612, the p-value is 0.108, and the T-table value is 1.669 with the original value of -0.407 and indirectly has an insignificant effect on the value of the company in the presence of profitability as a moderation variable.